Genetic data and meteorological conditions suggesting windborne transmission of H5N1 high-pathogenicity avian influenza between commercial poultry outbreaks - Alexander Nagy; Lenka Černíková; Kamil Sedlák (PLoS ONE, 2025)
Understanding the transmission routes of high-pathogenicity avian influenza (HPAI) is crucial for developing effective control measures to prevent its spread. In this context, windborne transmission, the idea that the virus could travel through the air over considerable distances, is a contentious concept, and documented cases have been rare. Here, though, we provide genetic evidence supporting the feasibility of windborne transmission. During the 2023−24 HPAI season, molecular surveillance identified identical H5N1 strains among a cluster of unrelated commercial farms about 8 km apart in the Czech Republic. The episode started with the abrupt mortality of fattening ducks on one farm. This was followed by disease outbreaks at two nearby high-biosecurity chicken farms. Using genetic, epizootiological, meteorological and geographical data, we reconstructed a mosaic of events strongly suggesting wind was the most probable mechanism of infection transmission between poultry in at least two independent cases. By aligning the genetic and meteorological data with critical outbreak events, we determined the most likely time window during which the transmission occurred and inferred the sequence of infected houses at the recipient sites. Our results suggest that the contaminated plume emitted from the infected fattening duck farm was the critical medium of HPAI transmission, rather than the dust generated during depopulation. Furthermore, our results also strongly implicate the role of confined mechanically-ventilated buildings with high population densities in facilitating windborne transmission and propagating virus concentrations below the minimum infectious dose at the recipient sites. These findings underscore the importance of considering windborne spread in future outbreak mitigation strategies.